Electrical, morphological and structural properties of Ti ohmic contacts formed on n-type 4H–SiC by laser thermal annealing. (15th November 2022) - Berger, Clément; Alquier, Daniel; Bah, Micka; Michaud, Jean-François
Abstract: This work focuses on the obtention of good ohmic contact using laser annealing on a titanium (Ti) layer deposited on n-type 4H–SiC. After the Ti deposition, the contacts were annealed by UV laser irradiation with energy densities ranging from 2.0 to 5.0 Jcm −2 at 30 kHz and 800 mm s −1 . Local electrical measurements indicated a uniform current conduction of the irradiated area, independently to the contact topology. A specific contact resistance, determined by circular-TLM patterns, as low as 1.0 × 10 −4 Ω cm 2 was reached for a Ti layer annealed at 5.0 J cm −2 . This value is comparable with a Ti/Ni contact annealed by RTA and is 4 times lower than the one of previous works using Ti laser annealing. The structural investigation demonstrated that the ohmic transition occurs as soon as the TiC phase appears. The improvement of the ohmic properties could be attributed to the preferential alignment onto 4H–SiC of larger and larger TiC grains at the interface. Morphological measurements indicated that the contact surface can be strongly impacted by a high energy irradiation while the contact composition, mainly formed of TiC, is kept once the ohmicity threshold is reached. These results will help to improve the next generation of vertical devices. Graphical abstract: Image 1